Modeling seasonal wind pattern from imaging and non-imaging data / Siti Noratiqah Mohamad Deros - Mohamad Deros, Siti Noratiqah (Institute of Graduate Studies, UiTM, 2017)
Wind speed in Malaysia is categorized as low with annual mean of 3-5 m/s and influenced primarily by four monsoon season; Northeast and Southwest monsoon with two transition period; April and October inter monsoon. Monsoon seasons were classified based on the origin of wind blows that brings unique character of wind speed and direction. Current wind study utilized limited wind data to projects wind behavior in wind pattern model generation. Short-term wind data insufficient to explain wind criteria by neglects the seasonality behavior of wind caused by different monsoon season. Wind observation using ground measurement devices such as anemometer and wind vane produced limited spatial resolution data that initiated the used of imagery data with 100-150 km2 swath width. Wind direction extraction using wavelet transform (WT) technique is an example of wind study using imagery data. However, the study focused on high wind speed area due to the limitations of wavelet coefficient derivation that requires minimum 7 m/s wind speed and underestimates streak produced by lower speed. This study attempts to develop wind pattern model by forecasting the seasonal wind speed, determine the seasonal wind speed distribution model and extract wind direction from SAR images acquired at low wind speed area. The study site represents the seasonal and low wind speed condition in Pulau Langkawi, Malaysia…